O lugar do camponês e questão agrária na Revolução Russa de 1917 / The place of the peasant and the "land question" in the Russian revolution of 1917 - Tavares, Ana Claudia Diogo; Trotta Dallalana Quintans, Mariana (Revista Direito e Práxis, 2017)
DOI:10.1590/2179-8966/2017/30243 Resumo No ano do centenário da Revolução Russa de 1917, o artigo procura revisitar os escritos de Vladimir Ilitch Uliánov (1870-1923), Lenin, sobre os camponeses e a questão agrária na Rússia ao longo dos acontecimentos que abalaram o mundo no ano de 1917. Em síntese, refletimos sobre as persistências e inflexões do pensamento lenineano que influenciaram a práxis do partido bolchevique em relação ao campesinato. Palavras- chave: Revolução russa; Camponeses; Questão agrária. Abstract In the year of the centenary of the Russian Revolution of 1917, the article seeks to revisit the writings of Vladimir Ilitch Ulyanov (1870-1923), Lenin, on peasants and the land question in Russia throughout the events that shook the world in the year 1917. In summary, we reflect on the persistences and inflections of Lenin’s thought that influenced the praxis of the Bolshevik party’s in relation to the peasantry. Keywords: Russian revolution; Peasants; Land question.